Optical Properties Transformation under Laser Treatment of Hybrid Organic–Inorganic Thin Films. Issue 4 (2nd January 2019) - Saifutyarov, Rasim; Petrova, Olga; Taydakov, Ilya; Akkuzina, Alina; Barkanov, Artem; Zykova, Marina; Lipatiev, Alexey; Sigaev, Vladimir; Avetisov, Roman; Korshunov, Vladislav; Avetissov, Igor
Abstract : Thin films (50–100 nm) of hybrid materials (HM's) based on inorganic matrices and organic phosphor are prepared by layer‐by‐layer vacuum deposition on glass substrates. The possibility of an exchange solid‐phase reaction between the organometallic phosphor (tris‐(8‐hydroxyquinolate) aluminum) and inorganic compounds without thermal heating of the sample volume is demonstrated. The reaction is stimulated by Pharos SP laser (1030 nm wavelength, 180 fs pulse duration, 100 kHz pulse repetition rate, maximum power 6 W) with localization of the reaction region to the focused laser beam waist (diameter of ≈1 µm). The resulting products have a photoluminescence (PL) intensity exceeding the PL intensity of the original organometallic phosphor. Local modification of HM's thin films by femtosecond laser beam allows creating 2D integrated optics elements. Abstract : Thin films of hybrid materials based on inorganic matrices and organic phosphor are prepared by layer‐by‐layer vacuum sputtering on a glass substrates. The possibility of an localized exchange solid‐phase reaction between the organometallic phosphor (tris‐(8‐hydroxyquinolate) aluminum) and inorganic compounds stimulated by femtosecond laser is demonstrated. The resulting products have a photoluminescence intensity exceeding that one of the original organometallic phosphor.